Colorectal Cancer in Inflammatory Bowel Disease - Stidham, Ryan W.; Higgins, Peter D.R. (Clinics in Colon and Rectal Surgery, 2018)
Patients with inflammatory bowel disease (IBD) are at significantly increased risk of colorectal cancer (CRC), principally resulting from the pro-neoplastic effects of chronic intestinal inflammation. Epidemiologic studies continue to highlight the increased risk of CRC in IBD. However, the incidence has declined over the past 30 years, attributed to both successful CRC-surveillance programs and improved control of mucosal inflammation. Risk factors that further increase the risk of IBD-related CRC include disease duration, extent and severity, the presence of inflammatory pseudopolyps, coexistent primary sclerosing cholangitis, and a family history of CRC. All major professional societies agree that IBD-CRC surveillance should occur more frequently than in the general population. Yet, guidelines and consensus statements differ on the surveillance schedule and preferred method of surveillance. Improved sensitivity to previously “invisible” flat dysplastic lesions using high definition and chromoendoscopy methods has resulted in many guidelines abandoning requirements for random untargeted biopsies of the colon. While colonic dysplasia remains a worrisome finding, and several clinical scenarios remain best addressed by total proctocolectomy due to concerns of synchronous undetected lesions and the unpredictable tempo of progression to malignancy, better detection techniques have also increased opportunities for endoscopic resection of dysplastic lesions that can be clearly delineated. Finally, the expanding armamentarium of medical options in IBD, including anti-tumor necrosis factor and anti-adhesion biologic therapies, have substantially improved our ability to control severe inflammation and likely reduce the risk of CRC over time.
Keywords: inflammatory bowel disease; Crohn's disease; ulcerative colitis; colorectal cancer; dysplasia; chromoendoscopy; chemoprevention